2003
DOI: 10.1177/0021998303037005053
|View full text |Cite
|
Sign up to set email alerts
|

Modified Short Beam Shear Test for Measurement of Interlaminar Shear Strength of Composites

Abstract: A modified short beam shear test was proposed to measure interlaminar shear strength (ILSS) of fiber reinforced carbon-carbon composites (CCC). The direct loading in the short beam shear (SBS) test is replaced by an indirect loading through a rubber pad and an aluminum seat. This loading reduced flexure stresses to less than one fourth of the SBS test and eliminated transverse shear stress concentration under the load point. Both beam and contact finite element analyses were conducted to validate the proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 9 publications
2
31
0
1
Order By: Relevance
“…Three main types of damage modes were identified in each of the four composite architectures; localized damage beneath the punch, tow cracks along the bottom of the specimen, and delamination between the various tows and yarns. The localized damage is caused by the large stress concentration just beneath the central punch [20] resulting in crushing of the matrix and fiber damage in the tows. A tensile stress is generated at the bottom of the specimen due to the bending moment.…”
Section: Optical Micrographsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three main types of damage modes were identified in each of the four composite architectures; localized damage beneath the punch, tow cracks along the bottom of the specimen, and delamination between the various tows and yarns. The localized damage is caused by the large stress concentration just beneath the central punch [20] resulting in crushing of the matrix and fiber damage in the tows. A tensile stress is generated at the bottom of the specimen due to the bending moment.…”
Section: Optical Micrographsmentioning
confidence: 99%
“…To reduce this contact stress and create a more uniform load distribution, four-point [17] bending and five-point [19] bending fixtures have been adopted. Other limitations to the use of SBS testing include a greatly underestimated ILSS of the material [17,20,21] due to the simplified assumption of shear flow equations which neglect the effect of concentrated load. Despite these disadvantages, SBS continues to be a useful test for qualitative comparison of the behavior of different material architectures as well as for quality control [17,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traulis et al [6] found that using z-pins, ILSS increased fairly. However, Abate et al [7] have reported that these techniques are labor intensive and require additional manufacturing processes that can significantly increase the cost of resulting component. Many researchers have explored other ways to improve ILSS by using nano, micro and macro fillers such as carbon nanotubes, graphene, micro Al2O3, SiO2, Ti2O3, short carbon fibers etc.…”
Section: Introductionmentioning
confidence: 99%
“…Akay et al [2] noticed the degradation of matrix and hence decrease in ILSS property of carbon fiber reinforced bismaleimide on long term exposure to high temperature. Abali et al [3] had modified short beam shear test for measurement of inter-laminar shear strength of composites. Reddy et al [4] conducted experiments to find the flexural, compressive and ILSS properties of Kapok/ Glass composite.…”
Section: Introductionmentioning
confidence: 99%